2011
DOI: 10.1186/1743-0003-8-23
|View full text |Cite
|
Sign up to set email alerts
|

Markedly impaired bilateral coordination of gait in post-stroke patients: Is this deficit distinct from asymmetry? A cohort study

Abstract: BackgroundMultiple aspects of gait are typically impaired post-stroke. Asymmetric gait is common as a consequence of unilateral brain lesions. The relationship between the resulting asymmetric gait and impairments in the ability to properly coordinate the reciprocal stepping activation of the legs is not clear. The objective of this exploratory study is to quantify the effects of hemiparesis on two putatively independent aspects of the bilateral coordination of gait to gain insight into mechanisms and their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
42
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 35 publications
(43 reference statements)
6
42
0
5
Order By: Relevance
“…"Estimation of Gait Independence Using a Tri-Axial Accelerometer in Stroke Patients" by Kijima Y et al Journal of Aging and Physical Activity © 2017 Human Kinetics, Inc. Stroke patients walked more slowly than the control group, and the dependent group walked significantly more slowly than independent group; these results were consistent with a previous report (Meijer et al, 2011). A study has suggested the importance of gait velocity to assess the gait ability in stroke patients (Schmid et al, 2007), and gait velocity has a large influence on acceleration (Henriksen et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…"Estimation of Gait Independence Using a Tri-Axial Accelerometer in Stroke Patients" by Kijima Y et al Journal of Aging and Physical Activity © 2017 Human Kinetics, Inc. Stroke patients walked more slowly than the control group, and the dependent group walked significantly more slowly than independent group; these results were consistent with a previous report (Meijer et al, 2011). A study has suggested the importance of gait velocity to assess the gait ability in stroke patients (Schmid et al, 2007), and gait velocity has a large influence on acceleration (Henriksen et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…Gait regularity in all directions of the trunk and unaffected thigh and in the VT direction of the affected thigh was decreased in the dependent group compared with the independent and control groups, consistent with previous studies (Meijer et al, 2011;Mizuike et al, 2009). In comparisons excluding the effect of gait velocity, gait symmetry, calculated from an acceleration in AP and VT directions of the trunk and in the VT direction of the thigh, was decreased in the dependent group compared with the independent and control groups.…”
Section: Discussionsupporting
confidence: 89%
“…This preference for the non-paretic limb is also reported during other daily transfers, such as sit-to-stand and stand-to-sit [12], and during gait initiation from standing [21]. Similar interlimb dys-coordination, as in the present study, has been demonstrated during walking post-stroke as impaired leftright stepping coordination [22], and impaired processing of afferent input between the two body sides [23]. These atypical characteristics of gait post-stroke are suggested to be distinct properties that should be targeted in rehabilitation [22,23].…”
Section: Discussionsupporting
confidence: 81%
“…3 As a result, gait patterns become asymmetrical and gait speed reduced. 4 Additionally, impaired walking is commonly observed beyond 6 months after stroke. 5 This lack of walking competency can precipitate and exacerbate a sedentary lifestyle and cardiovascular deconditioning.…”
mentioning
confidence: 99%